Of men and marshes - Errington, Paul L. (Paul Lester), 1902-1962 (Bur oak book., 2012)
Standing with such environmental classics as Loren Eiseley's The Immense Journey, his friend and mentor Aldo Leopold's A Sand County Almanac, and Joseph Wood Krutch's The Voice of the Desert, Paul Errington's Of Men and Marshes remains an evocative reminder of the great beauty and intrinsic value of the glacial marshland. Steeped in insights from Errington's biological fieldwork, his experiences as a hunter and trapper, and his days exploring the marshes of his rural South Dakota childhood, this vibrant work of nature writing reveals his deep knowledge of the marshland environments he championed.